An Outlook onto the Interest-Free Housing Financing Systems in Turkey through the Financial Legal Stratagems Axis - Sefer Korkmaz (İslam Tetkikleri Dergisi)
Financial legal stratagems have continued to be one of the areas of preoccupation of the fuqahā since the early stages of the substantive fiqh stratagem. These stratagems aim to find a legitimate solution to the interest ban by associating a loan contract with an exchange contract. These stratagems, which took an institutional guise during the Ottoman period, have preserved their actual value until today. This study, tried to prove that the activities of some of today’s interest-free financial institutions in the context of housing finance are largely based on the same financial stratagems. What makes our study different is that, contrary to the negative attitude in current academic studies, these stratagems can be a very functional solution to the interest prohibition when they are implemented with a good institutional mechanism. The stratagems of participating banksand savings institutions in the field of housing finance, which operate primarily in Turkey and have a wide place in the society; were examined to make a concrete claim. Then, current evaluations of these stratagems were discussed. Finally, some solutions were proposed by pointing out the potential functionality of fiscal methods for providing interest-free financing.